Giant congenital melanocytic naevus caused by NRAS Q61K mosaicism - Carl M. Thielmann; Antje Kampmeier; Alma Küchler; Martin Zenker; Ilse Wieland; Johanna Matull; Frederik Krefting; Klaus Griewank; Eva Hadaschik (Wiley, 2022)
Abstract Giant congenital melanocytic naevi (CMN) are large melanocytic lesions commonly associated with neurologic abnormalities. Patients diagnosed with giant melanocytic naevi are at an increased risk of developing melanoma compared to patients with smaller congenital naevi. If patients develop central nervous system (CNS) lesions and exhibit certain characteristic facial features, then the diagnosis of CMN syndrome can be made. We here present the case of a 24‐year‐old female who presented with multiple melanocytic naevi, which had been apparent since birth, and was diagnosed with giant melanocytic naevi caused by NRAS Q61K mosaicism. Both close follow‐up of imaging and clinical study is important so as not to miss cutaneous malignancy and CNS lesions.